The womanist idea - Maparyan, Layli (New York, NY : Routledge, 2012)
"Following on the heels of The Womanist Reader, The Womanist Idea offers a comprehensive, systematic analysis of womanism, including a detailed discussion of the womanist worldview (cosmology, ontology, epistemology, logic, axiology, and methodology) and its implications for activism. From a womanist perspective, social and ecological change is necessarily undergirded by spirituality - as distinct from religion per se - which invokes a metaphysically informed approach to activism."--Publisher's website.
The metaphysical architecture of the womanist idea. Luxocracy : rule by light ; Womanist origins : reading Alice Walker, Chikwenye Okonjo Ogunyemi, and Clenora Hudson-Weems ; Womanist worldview/womanism as spiritual movement ; Womanist methodology : transforming consciousness, changing the world ; A spiritual archaeology of the womanist idea ; Spiritual activism : a womanist approach -- Women's spiritual activism : five case studies. Transforming war into peace : Sister Chan Khong and Learning true love ; The alchemy of forgiveness : Immaculée Ilibagiza and Left to tell ; Turning a prison into an ashram : Kiran Bedi and It's always possible ; Speaking truth inside power : Pregs Govender's Love and courage ; Spiritualized sustainability : Wangari Maathai, Unbowed, and The green belt movement.
Includes bibliographical references (pages 368-377) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Spiritual life; Womanism; Mysticism; Social change; Electronic books